New cell lines expanding the diversity of Ewing sarcoma models - Kerkhoff, Maximilian; Schaefer, Christiane; Dirks, Wilhelm G.; Krzeciesa, Dawid; Bretschneider, Maximilian; Plaumann, Pauline R.; Guder, Wiebke K.; Streitbürger, Arne; Herter, Sonja; Peterziel, Heike; Oehme, Ina; Zahnow, Felina; et al. (International journal of cancer, 2025)
Ewing sarcoma (EwS) is a highly aggressive, malignant, solid tumor of childhood, and adolescence. Most EwS develop in bone, while it originates from connective, adipose, or muscle tissue less frequently. We report the establishment of new human EwS cell lines, all of which carry a t(11;22)(q24;q12) translocation generating the oncogenic transcription factor EWSR1::FLI1. Sequencing of the chimeric mRNAs indicated genomic DNA breakpoints localized in intron 8 of the EWSR1 gene and three different introns of the translocation partner gene FLI1. While three EwS cell lines carry the EWSR1::FLI1 fusions of ex7/ex6 (type I) or ex7/ex5 (type II), the EWSR1::FLI1 fusion variant ex7/ex7 (type IV) is described for the first time in a continuous EwS model. The cell lines presented genomic, epigenomic, and transcriptomic stability over a period of 6 months, though some variations in the chromosomal aberrations were observed in one cell line. TP53, STAG2, and CDKN2A/B mutations were the most frequent and most relevant mutations in our cell line panel. The TP53 mutational status seemed to have the biggest impact on drug sensitivity profiles. The new EwS models presented here may help to identify small molecule inhibitors that act directly on EWSR1::FLI1 fusion proteins or uncover other genetic vulnerabilities of the altered epigenome and transcriptome in EwS, which would contribute to a better understanding of Ewing sarcoma tumorigenesis.
Gesehen am 03.02.2026